PENGEMBANGANMODULFISIKA TOPIK GEJALAGELOMBANG DISEKOLAH MENENGAH ATAS (SMA) NEGERI3JAYAPURA - RUSTAMAJI, RUSTAMAJI; TRIWIYONO, TRIWIYONO (Jurnal Ilmu Pendidikan Indonesia, 2018)
This research aimed at creating module physics with the topic waves phenomenathatwasrelevanttobeusedatschoolthatcarryoutasystemofsks.Themethod usedwasresearchanddevelopmentwithphases:preliminary study (define),programdesigning (design) anddevelopment(develop).The module designwasbasedonthe resultof the preliminary study.Thentheprogramwasjudgedby expertsandpilottestedonthirty studentsof XI classofSeniorHighschool3Jayapura,usingonegrouppretest-posttestdesign.Thenwider scale tryoutusinga non-equivalentgrouppretest-posttestquasiexperimentaldesign,andwas conductedÂ on sixtyone students at theÂ sameÂ school. Conclusions ofÂ theÂ research were 1) characteristicsÂ oftheÂ modulephysics withÂ the topicwavesÂ phenomena,Â amongothers,self instructional,selfcontained,standalone,adaptive,anduserfriendly. 2)theapplication ofphysics modulewavesphenomenainthelearningtopicscansignificantlyimprovestudents'masteryofconcepts,3)prominenceofwavesphenomena,amongothers,haveacompletemodulestructure,equipped withthelearnerworksheets,completewithmathematicalequations,andsmartsolution.4)alimitation of thismoduleis not equipped with an exercise problems. Â Keywords: Research, physics module, students, phenomena.